Successful Profiling of Plasmodium falciparum var Gene Expression in Clinical Samples via a Custom Capture Array - Emily M. Stucke; Antoine Dara; Ankit Dwivedi; Theresa K. Hodges; Sandra Ott; Drissa Coulibaly; Abdoulaye K. Koné; Karim Traoré; Bouréima Guindo; Bourama M. Tangara; Amadou Niangaly; Modibo Daou; et al. (mSystems, 2021)
ABSTRACT var genes encode Plasmodium falciparum erythrocyte membrane protein-1 (PfEMP1) antigens. These highly diverse antigens are displayed on the surface of infected erythrocytes and play a critical role in immune evasion and sequestration of infected erythrocytes. Studies of var expression using non-leukocyte-depleted blood are challenging because of the predominance of host genetic material and lack of conserved var segments. Our goal was to enrich for parasite RNA, allowing de novo assembly of var genes and detection of expressed novel variants. We used two overall approaches: (i) enriching for total mRNA in the sequencing library preparations and (ii) enriching for parasite RNA with a custom capture array based on Roche’s SeqCap EZ enrichment system. The capture array was designed with probes based on the whole 3D7 reference genome and an additional >4,000 full-length var gene sequences from other P. falciparum strains. We tested each method on RNA samples from Malian children with severe or uncomplicated malaria infections. All reads mapping to the human genome were removed, the remaining reads were assembled de novo into transcripts, and from these, var-like transcripts were identified and annotated. The capture array produced the longest maximum length and largest numbers of var gene transcripts in each sample, particularly in samples with low parasitemia. Identifying the most-expressed var gene sequences in whole-blood clinical samples without the need for extensive processing or generating sample-specific reference genome data is critical for understanding the role of PfEMP1s in malaria pathogenesis. IMPORTANCE Malaria parasites display antigens on the surface of infected red blood cells in the human host that facilitate attachment to blood vessels, contributing to the severity of infection. These antigens are highly variable, allowing the parasite to evade the immune system. Identifying these expressed antigens is critical to understanding the development of severe malarial disease. However, clinical samples contain limited amounts of parasite genetic material, a challenge for sequencing efforts further compounded by the extreme diversity of the parasite surface antigens. We present a method that enriches for these antigen sequences in clinical samples using a custom capture array, requiring minimal processing in the field. While our results are focused on the malaria parasite Plasmodium falciparum, this approach has broad applicability to other highly diverse antigens from other parasites and pathogens such as those that cause giardiasis and leishmaniasis.